Systematic Study on Osmotic Drug Delivery Device Covering Design, Types, and Elements Imparting Zero Order Release (Asian Journal of Pharmaceutics (AJP), 2023)
Oral route is one of the most popular and successful delivery routes for the medicines. It achieved a prominentplace in drug delivery due to ease of administration by all age groups. The major disadvantage of oralconventional drug therapy is that, it has to be taken 2–3 times a day, and if patient misses any dose it leads toincomplete prescribed dose and delays the time of cure. The considerable efforts have been taken to improvethe success rate of oral drug delivery by modifying various parameters related to drug release. Osmosis isthe movement of a substance against concentration gradient; in this instance, osmotic delivery use an osmoticgradient to successfully distribute the drug in controlled way and with zero order kinetics and emerging as themost dependable method of regulated drug delivery. The medication release from device is mostly unaffectedby stomach secretions. Drug, release control polymer, osmotic agent, semipermeable membrane, and deliveryorifice are the major parts of osmotic delivery system. This review mainly focuses on an osmotic drug deliverysystem providing detailed information regarding its design, different types, and responsible ingredients forcontrolled release by the virtue of osmosis.